PENGARUH MANFAAT SELEKSI, KOMITMEN ORGANISASI DAN DISIPLIN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWANPADA HOTEL FIVELEMENTS RETREAT BALI - I Gusti Ayu BungaSangga Langit; Nyoman Mustika; Sapta Rini Widyawati (VALUES, 2023)
Human Resource Management (HR) is important in achieving the goals of a company with good human resources in the company, it will increase employee work productivity. Work productivity has an important role in achieving the goals of acompany. Based on the results of initial observations, the problems that exist at theHotel Fivelements Retreat Bali are violations of discipline during working hours which can be seen from the percentage of employee attendance. Lack of selection benefits, organizational commitment and work discipline. This research was conducted at the Hotel Fivelements Retreat Bali using a population and sample of 30 employees as research respondents. Data collection was carried out through observation, interviews, questionnaires and documentation studies. The data analysis technique used in this study was multiple linear regression analysis which was processed using SPSS version 25. Based on the results of the analysis, this study shows the benefits of selection, organizational commitment and work discipline have a positive and significant effect on employee work productivity at the Hotel Fivelements Retreat Bali so that the better the selection of employees, organizational commitment, and work discipline of employees within the company, the higher the work productivity of employees at the Hotel Fivelements Retreat Bali.